Local Content-Based Education as a Strategy for Post-Conflict Recovery and Drug Abuse Prevention in Marginalized Communities - Saifullah (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze the socio-educational impacts of conflict and drug vulnerability, evaluate the gap between the national curriculum and local needs, and develop a culturally rooted education model to promote social recovery and resilience. Using qualitative methods and an intrinsic case study design, the study involved 11 purposively selected participants, including educators, policymakers, and cultural leaders. Data were collected through in-depth interviews, participant observation, and document analysis using a validated interview guide and observation sheet. Analysis was conducted using an interactive model that included data reduction, data presentation, and conclusion drawing. Findings indicate that trauma, limited infrastructure, and cultural isolation hinder the effectiveness of formal education. In contrast, locally based agricultural education that integrates ethical and religious values increases student engagement and community resilience. The study concludes that a participatory local education model can serve as a strategic intervention in post-conflict recovery. The implications of this research suggest that education that integrates cultural values, traditions, and local wisdom can be an effective tool in rebuilding social cohesion and community identity, which have been weakened by conflict. Through this approach, communities can develop a stronger sense of character, a more profound sense of belonging, and a greater connection to their environment, thereby becoming more resilient to the threat of destructive behavior, including drug abuse.